Study of cases of post-partum hemorrhage after spontaneous vaginal delivery in labour room of obstetrics and gynecology department of tertiary care center, Ranchi, Jharkhand, India - Moitra, Bratati; Oraon, Bulllu Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Postpartum haemorrhage is one of the common causes of maternal death worldwide. Whenever the amount of blood loss from or into genital tract is 500 ml or more after delivery of baby or any amount of bleeding that makes patients haemodynamically unstable is post-partum haemorrhage. Methods: In this study amount of blood loss after spontaneous vaginal delivery was measured in 100 cases by calibrated blood drape. Patients having high risk criteria for PPH were excluded. Results: In this study 55% patients were from 20-30 years age group. 82% cases were nontribal. 94% belonged to lower middle class. 67% patients were primigravida. 89% patients had atonic PPH and 11% had traumatic PPH. 85% patients had mild PPH. 60% of atonic PPH was managed by oxytocin only. 10% required oxytocin + Methergin, 6% required oxytocin + Methergin + Misoprostol. 6% required Oxytocin + Methergin + Misoprostol + Carboprost. In this study surgical intervention was required in 18% cases. Blood transfusion was required in 74% cases. 75% cases were from non-tribal ethnicity. Conclusions: PPH is a life-threatening condition. If it can be diagnosed early and managed properly then many maternal lives can be saved. In this study there was no maternal death.